Aurora kinase A as a possible marker for endocrine resistance in early estrogen receptor positive breast cancer. (2nd January 2018) - Lykkesfeldt, Anne E.; Iversen, Benedikte R.; Jensen, Maj-Britt; Ejlertsen, Bent; Giobbie-Hurder, Anita; Reiter, Birgit E.; Kirkegaard, Tove; Rasmussen, Birgitte B.
Abstract: Background: Cell culture studies have disclosed that the mitotic Aurora kinase A is causally involved in both tamoxifen and aromatase inhibitor resistant cell growth and thus may be a potential new marker for endocrine resistance in the clinical setting. Material and methods: Archival tumor tissue was available from 1323 Danish patients with estrogen receptor (ER) positive primary breast cancer, who participated in the Breast International Group (BIG) 1-98 trial, comparing treatment with tamoxifen and letrozole and both in a sequence. The expression of Aurora A was determined by immunohistochemistry in 980 tumors and semi quantitively scored into three groups; negative/weak, moderate and high. The Aurora A expression levels were compared to other clinico-pathological parameters and outcome, defined as disease-free survival (DFS) and overall survival (OS). Results: High expression of Aurora A was found in 26.9% of patients and moderate in 57.0%. High expression was significantly associated with high malignancy grade and HER2 amplification. High Aurora A expression was significantly more frequent in ductal compared to lobular carcinomas. We found no significant association between Aurora A expression and DFS or OS and no evidence of interaction between Aurora A expression and benefits from tamoxifen versus letrozole. Conclusions: Aurora A expression in breast tumors was associated with high malignancy grade III and with HER2 amplification. A trend as a prognostic factor for OS was found in patients with high Aurora A expression. No predictive property was observed in this study with early breast cancer.